284 Genetic Selection Through Ecofeed Index Reduces Carbon Footprint in Heifers. (8th October 2021) - Kebreab, Ermias; Johnson, Jocelyn R R; Heuer, Claas; Deeb, Joseph
Abstract: Efficient feed conversion by ruminants has a direct impact on the animal's carbon footprint. The objective of this study was to determine the effect of using the EcoFeed ® index by STgenetics® to reduce methane production. The EcoFeed ® index is an integrated approach to genetic selection based on progeny testing of females for residual feed intake to identify animals who consume less feed while maintaining production compared to their herd mates to increase profitability and global sustainability. EcoFeed ® is moderately heritable and uncorrelated with traits currently selected for in dairy cows. A dataset containing phenotypic and genomic information on 5, 441 heifers was used for the analysis. Heifers were divided into low, medium and high EcoFeed ® classes based on ±0.5 SD from the mean. To estimate methane emissions, 17 mathematical models were collated from the literature. All models were subjected to evaluation of performance using an independent dataset containing 458 individual-animal methane production measurements. The model recommended by Intergovernmental Panel for Climate Change had the lowest root mean square prediction error with 1% mean bias and 3.37% slope bias. This model was used to calculate emissions from low and high EcoFeed® heifers. In addition, an average of all model results was computed and used to compare different classes of heifers. Based on dietary information and feed intake, low and high EcoFeed ® heifers were estimated to produce 194 and 164 g methane/d, respectively, using the selected model. Using model averages, the estimated methane production was 186 and 162 g methane/d, for low and high EcoFeed ® heifers, respectively. The reduction in emission between low and high EcoFeed ® classes was 12.6 to 15.4%. If savings from crop production were to be considered, there will be further reductions in the carbon footprint. Therefore, genomic selection is a powerful tool to reduce carbon footprint in ruminants.